When one is singular: Notes on zero-person constructions in Latvian - Nau, Nicole (Vilnius University Open Series, 2021)
Axel Holvoet has demonstrated that Latvian has two types of zero-person constructions which formally differ in grammatical number, and that the singular type has a parallel in Finnic, but not in Lithuanian. This paper shows that the meanings covered by the two types are distinct and do not overlap. Using the framework proposed by Gast and van der Auwera for the description of human impersonal pronouns, it is shown that the singular type is characterized by non-veridicality and an internal perspective. As in Finnish, but not Estonian, it is used in conditional sentences with all kinds of verbs. The plural type is used in Latvian as well as in Lithuanian with veridical propositions and an external perspective.